Construcción y parametrización funcional de un prototipo de aerogenerador de eje vertical. - Quezada Sarango, Hamilton Eduardo (2012)
The main objective of this work consists on building and parameters an aerogenerador of vertical axis for the laboratory of renewable energy of the career Electromechanical Engineering of the Area of the Energy, the Industries and the Natural Resources not Renewable of the National University of Loja, for its use and better development, as well as for the formation and feedback of the knowledge of the future generations of students of this fruitful career. The used methodology begins with the construction of the aerodynamic parts of the aerogenerador, considering a helix model, in order to obtain a satisfactory answer of the same one. Well-known the results of the calculations, among which the value of energy production and the operation of the aerogenerador is, are carried out an economic evaluation that considers the cost of building this eolic machine. With this you conclude the feasibility of the use of this aerogeneradores type like solution to the electric supply inside rural areas, climatically capable.